2007
DOI: 10.1177/0009922807303894
|View full text |Cite
|
Sign up to set email alerts
|

Physician Recommendations Regarding SIDS Risk Reduction: A National Survey of Pediatricians and Family Physicians

Abstract: Knowledge about recommended infant sleep position is relatively high, but there are gaps in physician knowledge regarding safe sleep recommendations. Greater dissemination of information is required, and barriers to implementation need to be identified and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Although many doctors and nurses were reported not to give any advice about sleep position, an alarming proportion (about 1 in 7) were reported to give incorrect advice. These data are consistent with a recent study by Moon et al27 in which only 69% of doctors who care for infants self reported advising exclusively supine sleep. This incorrect advice may have an important effect on infant sleep position; we found that advice not exclusively supporting supine sleep position from a nurse is associated with lower odds that an infant will be placed on its back to sleep.…”
Section: Commentsupporting
confidence: 93%
“…Although many doctors and nurses were reported not to give any advice about sleep position, an alarming proportion (about 1 in 7) were reported to give incorrect advice. These data are consistent with a recent study by Moon et al27 in which only 69% of doctors who care for infants self reported advising exclusively supine sleep. This incorrect advice may have an important effect on infant sleep position; we found that advice not exclusively supporting supine sleep position from a nurse is associated with lower odds that an infant will be placed on its back to sleep.…”
Section: Commentsupporting
confidence: 93%
“…Perhaps it is unsurprising that parental knowledge of the role of pacifiers was less than for the other recommendations; the same is true of health care providers (Moon et al, 2007; Eron et al, 2011). The better known recommendations substantially predate the pacifier use recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…9 This finding is consistent with other work, indicating that only 61% of pediatricians and 46% of family practice physicians discuss sleep position at each visit. 19 Prior work has also indicated that whether parents received advice about sleep position and what type of advice they received varied by practice location. Ray and colleagues 20 reported that parents who received care in a private practice setting were more likely to receive the correct instructions on sleep position compared with parents receiving care at an inner-city clinic.…”
Section: Discussionmentioning
confidence: 99%